Microbial mechanism of soil carbon emission reduction in maize-pea intercropping system with no tillage in arid land areas of northwestern China - Wang, Qi-ming; Chai, Qiang; Dou, Xue-cheng; Yin, Wen; Sun, Ya-li; Hu, Fa-long; Li, Han-ting; Liu, Zhi-peng; Wei, Jin-gui; Xu, Xiao-hui (Frontiers in Sustainable Food Systems, 2024)
Reducing carbon emissions from agricultural soils contributes to global greenhouse mitigation. Although the integration of no-tillage practices into maize/pea intercropping systems can achieve this reduction, the specific microbial mechanisms involved remain unclear. This study aimed to explore the effects of integrating maize/pea intercropping and no-tillage technologies on soil carbon emissions and microbial communities. The results indicated that intercropping no-till maize with peas reduced the average soil respiration rates by 19%. In 2021 and 2022, intercropping no-till maize with peas decreased soil carbon emissions by 25.1 and 30.4%, respectively. This practice resulted in a reduction of soil microbiota carbon and nitrogen by 26.9 and 19.7%, respectively, while simultaneously increasing the soil microbial gene beta diversity. Proteobacteria, Actinobacteria, Planctomycetes, Firmicutes, Bacteroidetes, and Acidobacteria collectively represented over 95% of the population and were predominant across all treatments. Intercropping no-till maize with peas decreased the abundance of carbohydrate-active enzymes in the soil. The structural equation modeling indicated that combined no-tillage and intercropping practices effectively decreased soil carbon emissions by modulating the community structure of soil microorganisms. This affected the abundance of carbohydrate-active enzymes and carbon-metabolizing genes in the soil. This study indicated that no-tillage and intercropping methods contributed to carbon reduction by influencing soil microbes. This study can provide microbial-level insights for refining agronomic practices to mitigate soil carbon emissions.